Gaining System-Product knowledge and Receiving Training Services-Organisational Consumers’ Preferences for Service Provider,Reference Group and Self Service - Ganesh, S. K. G.; Bhat, M. S.; Kumar, R. B. (Indian Journal of Marketing, 2006)
Many Indian organisations have been involved in extensive computerisation of their functions, since the late 90s. After extensive computerisation of functions gained momentum, System products/Software packages providing business information solutions to various customer-organisations have become an integral part of many organisations. Outsourcing of computerisation functions has been the most preferred option for many organisations. Information system products (meant for business application purposes) are of many types-Standard packages or System products developed-to-order. For example, Small packages on Accounting, Sales & Distribution, etc., Large system products like Enterprise Resource Planning (ERP) systems and Other business solution products on specific functional areas. All these information system solution products meant for business applications would be hereinafter referred as ’Systems’ or ’System products’ in this paper. "System products" and "Related (system) training services" were taken up for the present study.